2020
DOI: 10.1037/xhp0000702
|View full text |Cite
|
Sign up to set email alerts
|

Competing for affection: Perceptual fluency and ambiguity solution.

Abstract: Human perceptual processes are highly efficient and rapidly extract information to enable fast and accurate responses. The fluency of these processes is reinforcing, meaning that easy-to-perceive objects are liked more as a result of misattribution of the reinforcement-affect to the object identity. However, some critical processes are disfluent yet their completion can be reinforcing leading to object preference through a different route. One such example is identification of objects from camouflage. In a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 34 publications
(57 reference statements)
0
13
0
Order By: Relevance
“…Irrespective of this, we show for the first time that the enjoyment of stimuli that enable basic perceptual processes is not the end-all be- Conversely, previous research has shown that the disruption of basic perceptual processes can cause negative affect and visual disappointment (Erle & Topolinski, 2019;Topolinski et al, 2015; Experiments 4 and 5), which might be of interest for some companies. cussed above, however, previous research also shows that such disruptions of perceptual processing can be seen as more interesting (Flavell et al, 2020). Thus, a more appropriate implication would be to tailor the basic perceptual properties of a company logo to the company's purpose.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Irrespective of this, we show for the first time that the enjoyment of stimuli that enable basic perceptual processes is not the end-all be- Conversely, previous research has shown that the disruption of basic perceptual processes can cause negative affect and visual disappointment (Erle & Topolinski, 2019;Topolinski et al, 2015; Experiments 4 and 5), which might be of interest for some companies. cussed above, however, previous research also shows that such disruptions of perceptual processing can be seen as more interesting (Flavell et al, 2020). Thus, a more appropriate implication would be to tailor the basic perceptual properties of a company logo to the company's purpose.…”
Section: Discussionmentioning
confidence: 98%
“…This fact has now garnered extensive empirical support for multiple illusions (Topolinski et al, 2015) both on selfreported and physiological measures (e.g., Erle et al, 2017). Such findings are especially impressive as they go against the notion of perceptual fluency (see Reber, Schwarz, & Winkielman, 2004;Reber, Winkielman, & Schwarz, 1998) As a caveat, recent research has shown that in some cases, more effortful perception positively affects preferences (Flavell, Over, & Tipper, 2020). In these studies, participants had to identify camouflaged stimuli as quickly as possible and subsequently had to indicate how much they liked or how interesting they found them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations